Malaysian building / Christopher Nyawai Jemat - Jemat, Christopher Nyawai (2022)
Putra World Trade Centre (PWTC) Kuala Lumpur is centrally located at the city of Kuala Lumpur and is the main exhibition center in Kuala Lumpur that hosts many local and international events and exhibitions. It was built in 1981 and was completed in 1984 and was officiated by the Malaysia Prime Minister at that time, Tun Dr Mahathir Muhammad. A special box for keeping jewelry, often decorated and containing several separate parts.